Making Disaster Safer A Gender and Vulnerability Approach - Alexander, Ronni; Wajjwalku, Siriporn (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited book was produced through a transnational and transdisciplinary UNESCO Chair Project on Gender and Vulnerability in Disaster Risk Reduction Support. Contributors come from five disaster-prone Asian countries, and the chapters reflect their rich knowledge and practical experience in disaster management and humanitarian assistance. The chapters, all with a focus on gender and vulnerability, illustrate that gender can make people, especially women, vulnerable. The chapters address the experiences of state and non-state actors responding to disaster and promoting recovery at the local level. However, while women and vulnerable people may be victims of disasters, they also serve as agents for recovery and voices for better disaster preparedness. In sharing both successes and failures, as well as suggestions for the future, this book speaks to the need for transdisciplinary knowledge and multilevel coordination, as well as full equality for all genders and respect for human rights, in order to cope with increasingly more frequent, intense, and complex emergencies. This book is of interest as a text to students in a variety of disciplines who are focusing on disaster and health emergencies, as well as to practitioners and others promoting disaster risk reduction and resilience.
Gender, Vulnerability and Disaster -- A Critical Introduction to Gender and Disaster: Learning from women survivors in Northeast Japan -- Mainstreaming Gender into Disaster Recovery Policy and Practice: A Case Study of the Post-Earthquake Period in Yogyakarta Special Province, Indonesia -- : Health Literacy about Covid-19 Prevention Among Women in Low-Income Families in Indonesia -- Vulnerability and Resilience of Indigenous Women in Taiwan after a Disaster: Rebuilding a community -- The Vulnerability of Farmers and Post-Disaster Occupational Recovery at the Local Level: Policy Directions and Practical Guidelines in Chiang Rai Province, Thailand -- Local Government Initiatives to Foster Post-Tsunami Resilience in a Rural Coastal Community in West Java, Indonesia -- Emergence of Unconventional Risks and Hazards: Building coping capacities for most at-risk urban communities: Focusing on Malaysia -- Toward Climate-Resilient Development and Management: Developing indicators of climate hazards in Malaysia -- Volunteerism and Disaster Resilience: Institutional Design for Reducing Migrant Workers' Vulnerability to Floods in Thailand -- Feeling and Drawing the Invisible: Identifying Vulnerability through Alternative Expressions of the 2011 Northeast Japan Disaster -- Looking Forward: Making Disaster Less Devastating.
Keywords: Political planning; Social policy; Sex; Medicine, Preventive; Health promotion; Public Policy; Global Social Policy; Gender Studies; Health Promotion and Disease Prevention